Prediction of Viscosity in Ternary Systems - Karia, Falguni; Baluja, Shipra (Asian Journal of Chemistry, 2010)
By using various empiricaI relations, which are applicable to binary liquid mixture, viscosities of three ternary liquid mixtures in different compositions have been evaluated theoretically. These theoretical values are compared with experimental values. It is observed that good agreement between experimental and theoretical values calculated by Bingham and Kendall is observed in benzene and toluene systems (except in 0.0322 composition) whereas in THF system, these deviations are higher. The values calculated by Arrhenius relation are highest in all the three systems.